Особливості організації житлового середовища у ценральній частині міста - Вербицька, У. Ю.; Verbytska, U. (Видавництво Львівської політехніки, 2018)
Описано особливості житлового середовища у центральних частинах великих міст, основні проблемні питання в організації комфортних умов проживання та тенденції вирішення у сучасному будівництві та реконструкції. Розглянуто основні проблеми організації житлового середовища в умовах високої щільності наявної забудови та забезпечення екологічних стандартів середовища.

The article considers features of residential architecture in the downtown areas of large cities. Described are the main problems in the organization of comfortable living conditions and trends of its resolving in modern construction and reconstruction. The article analyzes the establishment of the living environment in the conditions of high urban density and the problem of ensuring standard of living. Today, one of the most intensive construction activity in large cities is situated in the downtown areas. It can be explained by the attractiveness of areas with already developed urban infrastructure and high concentration of the population for investors, and on the other hand, with historically composed ideas about the prestige of real estate in the downtown. However, the housing development in the downtown is influenced by the high urban density, which makes it difficult to ensure the comfort of the living environment. The comfort of a living environment in the downtown area of large cities is a topical issue nowadays and is actively explored. The high level of education, culture and technological progress prompts a city resident to an active lifestyle, which in turn influences the organization of his dwelling. Shortage of space due to the high urban dencity is a main feature of the living environment in the downtown area and is a major problem factor. One of the most common causes of stress is overcrowding. Housing crowding in adults has been linked to social withdrawal, stress, and aggression. Recent research also suggests there might be a trickle-down effect for children raised in these spaces. It is proved that the shortage of space in the school and on the playground negatively affects the behavior of children, contributing to greater aggressiveness in some and the timid behavior of other children. Another problem in higher-density built environment is arrangement of recreational spaces and lack of green space. There is no shortage of evidence to showjust how important access to quality green open space is for health and wellbeing. To achieve the appropriate level of comfort in high density environment, several following trends can be identified: • The tendency to use underground space. Placement of infrastructure and other facilities underground presents an opportunity for realizing new functions in urban areas without destroying heritages or negatively impacting the surface environment, and at the same time brings opportunities for long-term improvements in the environmental impact of cities and more efficient use of space and resources. • Vertical greening and green roof, where green open spaces are integrated in buildings, structures, such as sky gardens, roof terraces and green atria. This adds another layer of space for recreation and gathering.
Specifics of living environment development in the downtown areas
Keywords: житло; центр міста; висока щільність забудови; комфорт житлового середовища; housing; downtown; high density; living standards; 728